Malba Tahan and the tale Adventure of the 35 camels: glimpsing interdisciplinary didactic possibilities in the classroom (Research, Society and Development, 2023)
Júlio César de Mello e Souza (1985-1974), popularized by the heteronomies Malba Tahan, is often remembered for his vast children's literary production, whose main characteristic is to intertwine mathematical knowledge to various contexts, giving rise to productions that are, until today, sources of popularization of mathematics in Brazil. With this, we have established as the general objective of this article, to make a study of the tale Adventure of the 35 camels, in order to understand the possible didactic potentialities of the tale for basic education. Our work is anchored from the perspective of some theorists, for example, Rodrigues; Santana; Lindolfo. In addition, we also took into account, for our study, the main guiding document of basic education, the BNCC. We seek to answer the following research question: what contributions can Malba Tahan's adventure tale of the 35 camels bring to the teaching of Portuguese language and mathematics in basic education? In methodological terms, this research can be understood as bibliographical, with a qualitative approach. As a result, we point out that the articulation between the narrative elements of the tale with the mathematical elements is able to inspire teaching situations that provide subjects with understanding of mathematical concepts, breaking the erroneous perception that mathematics and literature cannot be associated for the sake of teaching.